ANALYSIS OF QUALITATIVE INDICATORS OF CIDER, DEPENDING ON TECHNOLOGICAL MODES - Y. A. Timanovskiy; M. O. Moskalev (Современная наука и инновации)
Low alcohol drinks made from natural raw materials are widespread throughout the world, well-known examples are wine and cider. Indicators such as sugar and alcohol in the manufacturing process are important. As a result, research in this area presents a wide range of possibilities for introducing innovative technologies into production.